校園農場之食農教育：學習永續農業與土地親近感 Campus Farming and Agrifood Education: Learning Sustainable Agriculture and Kinship With the Land - 林季怡 Chi-I Lin; 李育諭 Yuh-Yuh Li (National Taiwan Normal University, 2023)
本研究探討如何透過食農教育培養大學生生態觀點，特別是拉近人與環境的距離。食農教育，除了永續農業概念的學習，最重要的是營造人與土地的親近關係，人與土地親近關係的認識，是環境倫理人文思維的深層實踐，不易在傳統教室教學環境中傳遞。本研究參考後實證教學方式，規劃小農場實作，作為永續農業概念教學的主要場域。教學理念為透過提供 學生農業耕作知識內容及經驗脈絡，並適當維持學生正向愉悅的學習感覺，從而產生對土地之親近感。本研究探討除了永續農業概念的學習，校園農場作為食農教育教案是否可以，以及如何可以讓學生產生土地親近感，並以概念圖及開放式意見調查進行資料蒐集，針對111位學生在學期初與學期末進行永續農業概念圖評量及開放式意見調查。主要研究發現包括：一、透過概念圖分析，學生對永續農業的概念在學期末測驗分數是提高的，且在環境或是經濟面向分數會較社會面向分數高；二、學生土地親近感在學期末測量分數相較於學期初提高，土地親近感之改變顯示食農教育課程有助於永續農業概念之學習；三、概念圖作為永續農業概念測量方法，具有不錯的效度。本研究建議，未來食農教育可規劃校園農場作為提供知識文化刺激的場域，增加學生與真實農業問題互動的機會與動機。 In the Global Education 2030 Agenda, United Nations Educational, Scientific and Cultural Organization (UNESCO, 2017) emphasized that addressing the imbalance between humans and nature and promoting sustainable agriculture to end hunger and ensure food security are among the most essential educational goals. Community-based agriculture can be a key driver of change (UNESCO, 2017). On April 22, 2015, the Japanese government began promoting food and agriculture education and established the Basic Act on the Promotion of Urban Agriculture. One of the proposed strategies in this act is to "start from education and establish roots." Similarly, on April 19, 2022, Taiwan established the Food and Agriculture Education Act, which was promulgated on May 4, 2022. According to Article 1 of the Food and Agriculture Education Act, the goals of food and agriculture education are to promote nationwide food and agriculture education; strengthen the link between diet, environment, and agriculture; enhance national health; inherit and promote a culture of food and agricultural; promote sustainable development of rural areas, agriculture, and the environment; establish a sound national food and agriculture education system; and cultivate talent. The fundamental goal of food and agriculture education is to strengthen the connection between diet, environment, and agriculture. One strategy to achieve this goal is to focus on strengthening the connection between humans and nature. The relationship between humans and the environment has not received considerable attention from scholars in the fields of the social sciences and humanities. However, scholars have begun to shift their focus toward the interaction between humans and the environment. Aldo Leopold, regarded as the father of environmental ethics, was the first scholar in the Western world to consider the relationship between humans and the environment. He introduced the concept of land ethics as a means of evaluating how humans should relate to their environment. According to Aldo Leopold's land ethics, humans are members of a biotic community and must maintain the integrity of the land. Leopold emphasized the importance of the land, arguing that it is not merely a resource for human use but rather a mutually interdependent ecological community. Expanding on these reflections regarding humanity, Zalasiewicz et al. (2010) observed that human history has transitioned from the Holocene epoch to the Anthropocene epoch, a transition that began in approximately 1750. Consequently, humans have become the primary agents shaping the Earth's environment. The challenge of the Anthropocene epoch, however, lies in the growing alienation between humans and the land, which has led to humans altering the natural environment and has posed a threat to the sustainable existence of human society. Seeking to understand the kinship between humans and the land represents a humanistic approach to environmental ethics. Such an approach can be challenging to employ in traditional classroom settings to achieve target learning outcomes. In the present study, we investigated how agrifood education can foster an ecological perspective in university students that strengthens the connection between humans and the environment. In addition to imparting the principles of sustainable agriculture, a key objective of agrifood education is cultivating a sense of kinship with the land. Our primary research question was as follows: Beyond the acquisition of knowledge regarding sustainable agriculture, how and to what extent does the integration of information regarding small-scale farming practices into agrifood curricula enhance students' sense of kinship with the land? In accordance with postpositivist approaches, we adopted a sustainability transdisciplinary education model as a teaching strategy and established a small campus farm. This small campus farm was established to facilitate on-site learning regarding sustainable agriculture and related practices. By directly involving students in the farming experience, we sought to create a positive and enjoyable learning environment and foster a deep connection with the land. The campus farm served as a platform for integrating interdisciplinary knowledge regarding agrifood. Situated within the university campus, it combined the elements of the land, natural vitality, and a communal space. It enabled the students to understand the importance of preserving the natural environment and enhanced their understanding of the inherent and interconnected relationships between individuals and society as well as between individuals and the environment. We used concept mapping and open-ended questions to gather research data at the beginning and end of a semester, and we analyzed data obtained from 111 undergraduate students. Concept maps were used to evaluate the students' understanding of sustainable agricultural development. Subsequently, these concept maps were independently evaluated by two experts on the basis of predetermined criteria, and the interrater reliability was determined. To measure the students' sense of connection to the land, an open-ended survey was conducted, and the textual content of the students' responses was analyzed. This survey was conducted at two time points: at the beginning of the study and at the end of the study. The first part involved a thematic apperception test similar to that used in psychology, in which the students were presented with an image of a piece of land and asked to record their thoughts and associations with the image. In the second part, students were presented with open-ended questions through which they were asked to express their ideas regarding different agricultural cultivation methods. The research participants primarily comprised university students enrolled in a two-semester general education course on food and agriculture. These students were affiliated with various colleges within the university, including the College of Science, College of Engineering, College of Marine Sciences, College of Management, College of Social Sciences, and College of the Humanities and Arts. Most of the students had only a basic understanding of agriculture, with a few having a family background in farming. Male students accounted for 57.7% of the participants, and female students accounted for 42.3%. The distribution among academic years was as follows: 25.2% freshmen, 36.9% sophomores, 2.7% juniors, and 35.5% seniors. Our results indicated the following. First, by the end of the course, the students' understanding of and their attitude toward sustainable agriculture considerably improved. Second, the students' sense of kinship with the land substantially improved. Third, the change in the students' attitudes toward sustainable agriculture and their sense of kinship with the land correlated with their on-site campus farming experience.